2021
DOI: 10.1016/j.ijpam.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent mental health disorders in the GCC

Abstract: Background The Gulf Cooperation Council (GCC), with a predominant ‘youth bulge’ among its 54 million people, has witnessed an exponential increase in research pertinent to child and adolescent mental health (CAMH). Aside from a few narrative reviews, to date, no critical appraisal examining the magnitude of CAMH has emerged from this region. Aims This study aimed to report the prevalence rates of CAMH disorders in the GCC through a systematic review of the existing lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 65 publications
4
28
1
Order By: Relevance
“…Subtypes according to the Diagnostic and Statistical Manual of Mental Disorders (5th edition) are inattention (being unable to keep focus), hyperactivity (excess movement that is not fitting to the setting) and impulsivity (hasty acts that occur without thought) [2]. Epidemiological studies indicate that ADHD is one of the most common mental disorders affecting children [3,4], with prevalence in the childhood-adolescent community ranging between 2% and 8% globally [5,6]. High prevalence rates persist in adult ADHD patients, into the range of 2.6% to 6.8% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Subtypes according to the Diagnostic and Statistical Manual of Mental Disorders (5th edition) are inattention (being unable to keep focus), hyperactivity (excess movement that is not fitting to the setting) and impulsivity (hasty acts that occur without thought) [2]. Epidemiological studies indicate that ADHD is one of the most common mental disorders affecting children [3,4], with prevalence in the childhood-adolescent community ranging between 2% and 8% globally [5,6]. High prevalence rates persist in adult ADHD patients, into the range of 2.6% to 6.8% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively, our data was lower than the results published in China, where the reported anxiety prevalence was 45.1% [ 22 ]. However, the results of our study show a higher prevalence than the expected anxiety level among adolescents in the GCC prior to the pandemic [ 4 ]. Furthermore, our prevalence was higher than the results reported in Saudi Arabia, Latin America, and Jordan among adolescents during the pandemic, which reported around 28% anxiety prevalence utilizing screening tools [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 79%
“…Specifically, anxiety disorder is the ninth leading global cause of disease and disability for adolescents [ 3 ]. A systematic review conducted among the six Gulf Cooperation Council (GCC) countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates) revealed that the pooled prevalence of anxiety ranged between 17.27% and 57.04% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 36,37 ] reported that around 3% and 9% of the participants have core features of generalized anxiety disorder. In a recent meta-analysis of six Arabian Gulf countries by Chan et al [ 38 ], out of the accrued 33 studies that ful lled study criteria, the pooled prevalence of anxiety symptoms ranged from 17.27% to 57.04%. This critical appraisal covered the pre-pandemic era.…”
Section: Resultsmentioning
confidence: 99%